2007
DOI: 10.1620/tjem.212.359
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Metabolic Syndrome Unfavorably Influences Oxidative Stress and Fatty Acid Metabolism in Men

Abstract: Metabolic syndrome (MS) is defined by the clustering of several components (MSC), which include abdominal fat accumulation, impaired glucose homeostasis, hypertriglyceridemia, lowered high-density lipoprotein cholesterol, increased blood pressure, and hyperuricemia. Metabolic syndrome is also accompanied by increased oxidative stress and inflammation as well as by altered composition of esterified fatty acids (FA). Therefore, we have investigated 210 men (categorized into six groups with increasing number of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…In this study, several anthropometric and biochemical characteristics of MetS correlated significantly with increased concentrations of CD-LDL, which reflect oxidation of the lipid component of LDL. This finding is in agreement with the results of our studies concerning the severity of MetS, oxidative stress, hypertriglyceridemia, and fatty acid metabolism [ 37 , 38 ]. The important role of lipid peroxidation in the pathogenesis of MetS has been proven in many experimental and clinical studies [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, several anthropometric and biochemical characteristics of MetS correlated significantly with increased concentrations of CD-LDL, which reflect oxidation of the lipid component of LDL. This finding is in agreement with the results of our studies concerning the severity of MetS, oxidative stress, hypertriglyceridemia, and fatty acid metabolism [ 37 , 38 ]. The important role of lipid peroxidation in the pathogenesis of MetS has been proven in many experimental and clinical studies [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…We showed C20:3n-6 and C20:4n-3 fatty acid levels to be higher and estimated D5D(n-6) activity to be lower in our subjects with than in those without MetS. Essentially the same results were reported for n-6 fatty acids and D5D(n-6) by Zak et al in the Czech Republic 28) and by Warenjö et al in a Swedish 10) study population. We were not able to detect C18:3n-6, although its identification has been described in European reports.…”
Section: Discussionsupporting
confidence: 89%
“…PAF-like phospholipids are recognized in the atherogenic lipoproteins of small, dense LDL [38][39][40][41] . Zak et al reported that the severity of MetS was associated with the progression of oxidative stress, as evaluated with conjugated dienes in LDL 28) . Their results are consistent with the high TG/HDL-C ratio in our subjects with compared to without MetS.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the Δ6 desaturase products C18∶4 ω-3 and C18∶3 ω-6 might be compensatory to the decreases in C22∶5 ω-3, C22∶6 ω-3 and C20∶3 ω-6 up to C22∶5 ω-6. These alterations are also seen in the MetS [14], [22].…”
Section: Discussionmentioning
confidence: 73%